0276 Sleep EEG Changes in a Transgenic Mouse Model of Spinocerebellar Ataxia Type 3. (25th May 2022) - Tsimpanouli, Maria-Efstratia; Ghimire, Anjesh; Barget, Anna; Weston, Ridge; Costa, Maria do Carmo; Watson, Brendon
Abstract: Introduction: Spinocerebellar ataxia type 3 (SCA3) or Machado-Joseph disease is a fatal, incurable, dominantly inherited ataxia, typically of adult-onset, and the most frequent type of SCA worldwide. SCA3 patients show progressive neuronal loss in several brain areas reflecting a broad spectrum of motor and non-motor symptoms, including ataxia, parkinsonism, and sleep disorders. In other neurodegenerative diseases, sleep disturbances alter brain homeostatic mechanisms, including DNA repair, synaptic function, and network activity, leading to deterioration of neurologic function. Sleep research has provided insights into their pathophysiology, disease prediction, and symptom management. Such studies have not been performed in SCA3. The aim of this study is to characterize sleep EEG in an SCA3 transgenic mouse model. Methods: We used homozygous, hemizygous, and wild-type YACMJD84.2 littermate mice. To confirm the expected disease phenotype, we assessed for locomotor and exploratory activity in the morning and evening when the mice were 22 to 31 weeks old. We then implanted 6 electrodes in the frontal, parietal, and cerebellar areas. About two weeks after, we recorded their sleep activity for 15 hours (ZT0-15) per day for three consecutive days. We analyzed the data from the open-field testing and the EEG from the third day of recordings using SPSS and Matlab and a p<0.05 was considered for statistical significance. Results: As expected, homozygous SCA3 mice showed statistically significant decreased locomotor and exploratory activities compared with wild-type littermates. In terms of sleep architecture we did not observe any significant differences between the different genotypes. Moreover, compared with wild-type, homozygous SCA3 mice displayed increased β spectral power band activity during REM. They also had decreased θ band activity, β band activity, spindle activity, and γ band acitivity during wake. Conclusion: Our data suggest that EEG spectral power is dysregulated in homozygous SCA3 mice. Changes in β band have been observed in SCA3 patients during wake, and in patients with REM sleep behavior disorder. Therefore, future studies analyzing the sleep EEG of SCA3 patients are needed to confirm whether our findings are translatable. Further studies should also investigate the causal relationship between the observed differences in sleep and disease progression. Gaining greater insight into the role of sleep in SCA3 could provide translatable biomarkers and lead to improved assessment of the disease progression and therapeutic interventions. Support (If Any): NHLBI 5T32HL110952